Strategies for feeding tilapia in smallholder aquaculture systems: a study of aquaculture feed access and availability in two districts of Northern Province, Zambia - Johnson, J. W.; Jacobson, M.; Cole, S. M.; Kaminski, A. M.; Karsten, H.; Syapwaya, M.; Stauffer, J.; Jensen, L.; Lundeba, M. (Informa UK Limited, 2025)
Aquaculture contributes to agricultural development, economic growth, and poverty reduction initiatives in Zambia. In northern and rural regions of the country, development requires improvements to the management of local and farm-generated inputs. Fish farmers have limited market access and purchasing power, which restricts access to commercial inputs, such as formulated feeds and chemical fertilizers. Instead, farmers adopt integrated-agriculture-aquaculture (IAA) practices, whereby on-farm resources supply essential inputs. Research is limited regarding local systems of resource management, and this hinders development of innovations for improving efficiency. This mixed-methods study explored local patterns of resource utilization. Smallholders (n = 63) participated in surveys and interviews regarding resource management. A series of quantitative analyses, including descriptive statistics, principal component analyses (PCA), and multinomial logistic regression (logit) models, identified relationships between these resources, household livelihood, and system productivity. Qualitative analyses explored farmer perceptions regarding seasonal resource availability. Results suggested that livestock manure, homemade feeds comprising maize and soybean, garden residues, and kitchen wastes were the most frequently selected inputs. Logit models of feeding intensity found that income, proximity to Luwingu Town, experience in aquaculture, and access to extension services were key household resources. High-intensity feeding strategies incorporated commercial feeds, chemical fertilizers, as well as home-made feeds containing a wide diversity of both high- and low-quality ingredients. Low-intensity feeding strategies incorporated only farm waste and termites. Potential innovations that may improve system performance in resource poor contexts are considered and recommendations for additional research are offered.